PHO15 genes of Candida albicans and Candida parapsilosis encode HAD-type phosphatases dephosphorylating 2-phosphoglycolate. Issue 1 (10th October 2018) - Kročová, Eliška; Neradová, Sylva; Kupcik, Rudolf; Janovská, Sylva; Bílková, Zuzana; Heidingsfeld, Olga
Abstract: Most of the phosphatases of human fungal pathogens Candida albicans and C. parapsilosis have never been experimentally characterised, although dephosphorylation reactions are central to many biological processes. PHO15 genes of these yeasts have been annotated as the sequences encoding 4-nitrophenyl phosphatase, on the basis of homology to PHO13 gene from the bakers' yeast Saccharomyces cerevisiae. To examine the real function of these potential phosphatases from Candida spp., CaPho15p and CpPho15p were prepared using expression in Escherichia coli and characterised. They share the hallmark motifs of the haloacid dehalogenase superfamily, readily hydrolyse 4-nitrophenyl phosphate at pH 8–8.3 and require divalent cations (Mg 2+, Mn 2+ or Co 2+ ) as cofactors. CaPho15p and CpPho15p did not dephosphorylate phosphopeptides, but rather hydrolysed molecules related to carbohydrate metabolism. The preferred substrate for the both phosphatases was 2-phosphoglycolate. Among the other molecules tested, CaPho15 showed preference for glyceraldehyde phosphate and ß-glycerol phosphate, while CpPho15 dephosphorylated mainly 1, 3-dihydroxyacetone phosphate. This type of substrate specificity indicates that CaPho15 and CpPho15 may be a part of metabolic repair system of C. albicans and C. parapsilosis . Abstract : PHO15 genes of Candida albicans and C. parapsilosis encode HAD-type phosphatases, which have not been characterised as yet and dephosphorylate 2-phosphoglycolate.